The identification of small molecules that stimulate retinal pigment epithelial cells: potential novel therapeutic options for treating retinopathies. (1st February 2019) - Artero-Castro, Ana; Popelka, Stepan; Jendelova, Pavla; Motlik, Jan; Ardan, Taras; Rodriguez Jimenez, Francisco Javier; Erceg, Slaven
ABSTRACT: Introduction : Combinatory strategies using pharmacology and stem cell therapy have emerged due to their potential in the treatment of retinal pigment epithelium (RPE) cell related diseases, and a variety of different stem cell sources have been evaluated both in animal models and in humans. RPE cells derived from human embryonic stem cells (hESCs) and human induced pluripotent cells (hiPSCs) are already in clinical trials, holding great promise for the treatment of age-related macular disease (AMD) and hereditary RPE-related retinal dystrophies. Highly efficient protocol for RPE generations have been developed, but they are still time-consuming and laborious. Areas covered : The authors review RPE related diseases, as well as the known functions of RPE cells in retinal homeostasis. The authors also discuss small molecules that target RPE in vivo as well as in vitro to aid RPE differentiation from pluripotent stem cells clinically. The authors base this review on literature searches performed through PubMed. Expert opinion : Using high-throughput systems, technology will provide the possibility of identifying and optimizing molecules/drugs that could lead to faster and simpler protocols for RPE differentiation. This could be crucial in moving forward to create safer and more efficient RPE-based personalized therapies.